A Qualitative analysis the Factors Affects Voters Behavior - Suniadewi, Putu Ayu; Abadi, Mansurni (International Journal of Social and Political Sciences, 2025)
Understanding voter behavior in Indonesia's diverse sociopolitical landscape is critical for fostering democratic participation. This qualitative study examines the multifaceted factors influencing electoral choices in the 2024 Indonesian General Election through the lenses of sociological, psychological, and rational choice theories. Employing case studies, interviews, and thematic analysis of existing literature, the research highlights the interplay between Indonesia’s entrenched ethnic, religious, and social cleavages and emerging technological and demographic shifts. Key findings reveal a generational divide: urban, educated voters exhibit heightened skepticism toward institutional politics, while rural communities remain influenced by traditional patronage networks. The 2024 elections underscore the dual dynamics of digital campaign strategies such as the viral "gemoy" rebranding tactic targeting Gen Z and persistent structural challenges like political polarization and regional disparities in electoral access. The study identifies how digital platforms amplify emotional appeals and identity politics, yet rational calculations around policy outcomes (e.g., economic welfare programs) remain pivotal. Recommendations emphasize the need to strengthen electoral integrity through transparent governance, equitable technological access, and narratives that bridge pragmatic governance objectives with sociocultural values. By synthesizing multidisciplinary insights, this research contributes to broader discourses on inclusive political engagement in pluralistic democracies, offering pathways to mitigate polarization and enhance democratic resilience in Indonesia’s evolving political ecosystem.